Perampokan Menurut Perspektif Hukum Pidana Islam - Noor Fatma Zahura; Siti Khadijah; Sri Helma Hidayah; Lahmudinur (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This research aims to analyze robbery (ḥirābah) from the perspective of Islamic criminal law (fiqh jinayah), exploring its legal foundations, elements, and sanctions within the framework of the Qur’an, Hadith, and classical as well as contemporary jurisprudence. It addresses the relevance of Islamic principles in the context of Indonesia's positive law, particularly in combating violent crimes that threaten public safety. The study employs a qualitative-descriptive method with a normative juridical approach, specifically using doctrinal analysis to interpret primary Islamic legal sources (such as the Qur’an and Hadith) and secondary sources (classical fiqh works and contemporary journals). Comparative analysis is conducted with Indonesia's Criminal Code (KUHP), focusing on Article 365 regarding robbery, to identify similarities and differences in legal paradigms. The findings indicate that ḥirābah is classified as a ḥadd crime in Islamic law, endangering life and public safety (amān al-nās). Sanctions vary by severity, ranging from amputation to the death penalty, as outlined in Qur’an Surah al-Mā’idah (5):33. Comparatively, while KUHP emphasizes social protection and public order, Islamic law integrates divine justice and maqāṣid al-syarī‘ah to protect core human values (ḥifẓ al-nafs, ḥifẓ al-māl, etc.). The purpose of Islamic sanctions extends beyond retribution to deterrence and social harmony. This study concludes that integrating Islamic principles with positive law can enhance Indonesia's criminal justice system, promoting restorative justice aligned with Pancasila. Future research should explore empirical applications in Indonesian courts.